An Overview of Quiet Quitting Among Millennial and Gen Z Employees - Veren, Karissa; Callista, Ignacia; Aprillia, Aginta; Setradihardja, Lilenza Irawan; Prima, Ismoro Reza; -, Zamralita (Psikologi Prima, 2025)
Labor productivity in Indonesia is facing challenges following the COVID-19 pandemic, one of which is the growing phenomenon of quiet quitting. This phenomenon is one of the phases of disengagement, where employees only complete tasks according to the job description without any extra effort. Previous studies have shown that quiet quitting is becoming increasingly common following the pandemic and is more prevalent among Gen Z than among other generations. Additionally, work disengagement among the Millennial generation is also relatively high. If quiet quitting occurs on a massive scale, it can reduce innovation, increase the workload for engaged employees, and lead to stagnation in organizational growth. Therefore, further research is needed to understand how quiet quitting develops between the two generations. This study aims to describe the level of quiet quitting among Millennials and Gen Z. The research employs a quantitative method with a descriptive design. The sample was obtained through purposive sampling, comprising participants from the Millennial generation (born 1981 - 1996) and Gen Z (born 1997 -2012) who are currently working. Data were collected through an online survey using the Quiet Quitting Scale developed by (Galanis et al., 2023). The QQS measuring instrument consists of 9 items, with a Cronbach's Alpha reliability value of 0.773, indicating good consistency. The study included 105 research participants, comprising 40 Millennials and 65 Gen Z individuals. The results showed that the level of quiet quitting of Millennials and Gen Z tended to be low. The low level of quiet quitting among Gen Z and Millennials suggests that both groups remain highly engaged in their work. This research is expected to provide valuable insights for companies in designing effective strategies to increase employee engagement and mitigate the negative consequences of employee turnover.